Implications of Unregistered Polygamous Marriages For Children's Rights in Indonesia - Mutarofik, Mutarofik; Trigiyatno, Ali; Arifin, Ihyaul; Achmad, Musyafa; Azizah, Antik (Universitas Islam Negeri Sumatera Utara, 2024)
Polygamous marriages have become the latest issue regarding complaints about the impact of the practice of polygamy, where many husbands remarry without their wives' permission, some even do it secretly. Polygamy is still a debate in society. As a solution, some couples choose to carry out